The Role of Computerized Accounting in Improving Internal Audit Quality: Auditor's Perspective - Rosmayati, Siti (Yayasan Azka Hafidz Maulana, 2024)
This research explores the role of computerized accounting in improving the quality of internal audits, with a focus on process efficiency, data accuracy and better analytical capabilities. Through a qualitative approach and case study method, this research identifies how computer-based accounting systems help auditors carry out their duties more effectively. The research results show that this technology not only improves efficiency and accuracy in audits, but also facilitates comprehensive data analysis, enabling auditors to better identify and respond to risks. However, several challenges such as the need for adequate training, data security, and system integration need to be addressed to maximize the benefits of this technology. This research provides recommendations for overcoming these challenges and optimizing the use of computer-based accounting systems in internal audits.